Impact of fragment size variability on excavator efficiency in mining operations - M.V. Kachurovskyi; V.O. Sokolovskyi (Технічна інженерія)
This paper examines the impact of the granulometric composition of blasted rock on the performance of excavators in mining operations. Special attention is given to the effect of fragment size distribution, specifically logarithmic dispersion, on the loading cycle duration and excavator productivity. Chronometric observations were conducted at the Davydivskyi Granite Quarry, where WipFrag 3 software was used to measure the granulometric composition of the blasted rocks. It was determined that the average size of rock fragments and their dispersion significantly affect excavator productivity: as dispersion increases, the loading time increases due to higher resistance of the excavator bucket. With low dispersion (D = 0,8), excavator productivity decreases by 23,6 %, with medium dispersion (D = 1,0) by 27,1 %, and with high dispersion (D = 1,35) by 31 %. The study highlights the importance of reducing the variability in fragment sizes to improve the efficiency of excavators. The results of the research suggest that controlling the granulometric composition of blasted rock is crucial for maximizing excavator productivity, as reducing dispersion leads to decreased loading time and increased mining operation efficiency.